PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) DENGAN PENDEKATAN SAINTIFIK PADA MATERI SISTEM KOORDINASI KELAS XI SMA - Mayang Aprilia Trissa; Sa’diatul Fuadiyah; Syamsurizal Syamsurizal; Ria Anggriyani (Bioilmi: Jurnal Pendidikan, 2022)
The current development of education requires teachers to be able to innovate in making and creating various learning media. However, based on the results of observations, the learning media used were not effective and were not able to accommodate students to be active in the learning process. Development of Electronic Student Worksheets (e-LKPD) with a scientific approach to coordination system material for class XI high school students is an attempt to overcome problems found in the learning process. As well as helping students better understand the learning material, especially the coordination system material, because it includes material that is considered difficult. The development of this e-LKPD uses three stages of the 4d model, namely define, design, and develop. The subjects of this study consisted of two biology lecturers at Padang State University, one biology teacher and 31 students in class XI Science at State High School 1 Sungai Aur. The data collection instruments used were teacher interview questionnaires, student observation questionnaires, validity questionnaires, and practicality questionnaires. The results of e-worksheets validity test were 90.3% in the very valid category and the practicality test results were 91.4% in the very practical category. So that the developed e-worksheets meets the criteria and can be used in the biology learning process.